The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/rs10010064
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study of Soil Available Nutrient Simulation Using a Modified WOFOST Model and Time-Series Remote Sensing Observations

Abstract: Abstract:The approach of using multispectral remote sensing (RS) to estimate soil available nutrients (SANs) has been recently developed and shows promising results. This method overcomes the limitations of commonly used methods by building a statistical model that connects RS-based crop growth and nutrient content. However, the stability and accuracy of this model require improvement. In this article, we replaced the statistical model by integrating the World Food Studies (WOFOST) model and time series of rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Our previous study [ 44 ] showed that the empirical model can provide LAI estimates with higher accuracy than that of the physically based model (e.g., via PROSAIL simulation). In this study, the relationship between different VIs and ground LAI were analyzed, and the VI with the highest accuracy was selected to build a linear empirical model to estimate LAI.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study [ 44 ] showed that the empirical model can provide LAI estimates with higher accuracy than that of the physically based model (e.g., via PROSAIL simulation). In this study, the relationship between different VIs and ground LAI were analyzed, and the VI with the highest accuracy was selected to build a linear empirical model to estimate LAI.…”
Section: Methodsmentioning
confidence: 99%
“…Firstly, it can predict daily LAI by simulating CO 2 assimilation, respiration, leaf growth and dry matter formation. Secondly, following model modifications referred in [ 44 ], WOFOST can simulate LAI under nutrient-limited conditions. Compared with the water-limited LAI, the accuracy of estimated nutrient-limited LAI can be improved by eliminating the influence of SAN on crop growth.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnitude of the state update then depends on the uncertainty in both the model state and the observation. Examples of sequential approaches are the ensemble Kalman filter (EnKF) [5,8,[12][13][14]30,[40][41][42][43][44][45][46][47][48][49][50], particle filter (PF) [51], constant gain Kalman filter (CGKF) [52,53], and ensemble square root filter (EnSRF) [15,54]. For the state variables of sequential methods, LAI is also the most focused, followed by soil moisture content (SM).…”
Section: Introductionmentioning
confidence: 99%
“…The crop growth process and yield can be well simulated based on accurate model inputs, including climate, soil and agricultural management measures [24,25]. However, due to the spatial heterogeneity of field conditions, agricultural management, crop planting dates at regional scale, and the complexity of the land uses, the application of crop growth models was generally limited to small areas [26].…”
Section: Introductionmentioning
confidence: 99%